Legal Protection For Informal Workers In Realizing Decent Work To Achieve The Sustainable Development Goals - Imam Budi Santoso; Wiwin Triyunarti; Farhani, Athari; Faiqah Nur Azizah (Pandecta Research Law Journal, 2025)
Goal 8 of the Sustainable Development Goals aims to promote inclusive and sustainable economic development, provide full and productive employment, and ensure decent work for all individuals. Regrettably, in Indonesia, the concept of decent work encompassing social security, workers' rights, social dialogue, and employment is exclusively applicable to the formal economic sector, neglecting the informal economic sector, which comprises unregulated wage workers, employers, and homeworkers. Indeed, informal economic development is a fundamental foundation of the nation's economy. Achieving this type of decent work is a goal for sustainable development and would help support a lasting economy, as stated in Article 28, paragraph (2) of the constitution. This research seeks to examine the legal safeguards for labor and decent work, the realization of labor rights post-labor legislation, and the correlation between employment and sustainable development. The research methodology used is normative, using both a conceptual framework and an analysis of laws and regulations. This study's findings indicate a correlation between employment and sustainable development. An adept workforce may expedite the nation's developmental trajectory, enabling it to compete with more advanced nations. The results will positively influence the process of entering new markets.